Meal planning practices of young working mothers of pre-schoolers - Pelogo, Reizel C.
This qualitative research is a description of the meal planning practices of young working mothers with preschool children. The respondents were selected using purposive, specifically typical case, and snowball sampling methods. The researcher gathered qualitative data through a self administered questionnaire and one-on-one interview which utilized interview guide approach and think aloud method. Data were then analyzed using descriptive statistics and content analysis. Twenty five mothers, with ages ranging from 24 to 40, participated in the study. Most of them are college graduates and employees from government sector jobs. They are mothers of one to two preschoolers enrolled in selected preschools within Quezon City. The results showed that working mothers meal planning practices can be classified into two types daily and advance meal planners. Their meal planning includes deciding on dishes for the menu, scheduling when and where to buy ingredients, anticipating where to store food, and actual food preparation. Mothers consider highly their family's preference, the recipe attributes, family's health and nutrition, and budget in meal planning. Family's preference, specifically that of their preschoolers, is deemed the most important. Recipe attributes considered are the needed ingredients time needed to prepare, and variety. There are common problems encountered by mothers when planning meals. These are fatigue from work, difficulty in generating food ideas and choosing foods that are suitable for their children's taste. To manage family meals mothers receive help from family members as well as utilize some tools and strategies. It is important to note that in food-related chores, husbands contribute most in nuclear families but with the addition of family members such as in an extended family, grandmothers help out the most. Mothers identified computer as the top tool they use in meal planning mostly to search for new recipes online. They also employ strategies focused on planning meals and feeding their preschoolers. Based on the results of the study, it is more advantageous for working mothers to plan meals in advance. It is also recommended to develop meal planning tools, food guides, innovative and healthy foods, and user friendly phone applications that can help working mothers in planning and preparing family meals.